Research on the Influencing Factors of Mobile Government Users' Usage Intention Based on Meta-Analysis - Mu Guangyu; Deng Xiaobing; Li Zhaojin (Zhishi guanli luntan, 2023)
[Purpose/Significance] Many scholars have studied the influencing factors of mobile government users' usage intention. Reviewing a large amount of literature, we found that the existing empirical research results in this field are inconsistent. Therefore, we need to clarify further the primary factors and moderating variables that affect mobile government users' willingness and reveal the specific reasons for the differences in results. Finally, we will try to obtain the universal conclusion and provide a reference for improving the relevant theories and researches on user information behavior. [Method/Process] We selected 8 antecedent variables and 4 moderating variables affecting users' usage intention, 45 Chinese and foreign literatures, 27 795 samples, and 139 independent effect values in the meta-analysis. [Result/Conclusion] Performance expectation (r=0.586), effort expectation (r=0.538), trust (r=0.590), social influence (r=0.549), safety (r=0.489), compatibility (r=0.645), quality of service (r=0.588), and information quality (r=0.549) have significant positive effects on the usage intention of mobile government users. Group category, education level, social culture, and mobile government category moderate the relationship between the above 8 variables and mobile government users' usage intention.